Pengaruh Bahan Pencemar (Deterjen) Terhadap Kelangsungan Hidup Ikan Nila (Oreochromis niloticus) - Nurfina J. Pelu; Rosita Tabaika; Wirda Az Umagap (IAIN Ternate, 2022)
Detergent is a clothing cleanser that contains surfactants. Surfactants are active substances that are in the composition of detergents and are able to remove dirt on clothes. The effect of excessive use of detergents can damage the gills of fish, causing the survival of fish contained in water bodies cannot survive. If the water is polluted by high enough detergent, it can cause the tilapia icon to not be able to adapt until it finally collapses and dies. The purpose of this study was to determine the effect of pollutant (detergent) on the survival of tilapia and the concentration of the detergent that had the most effect and at what time the tilapia was lethal. The method in this study is a laboratory experiment. This research was conducted in the MIPA laboratory at IAIN Ternate with a room temperature of 29◦C, which was designed for 2 repetitions. The sample of tilapia used was 40 fish with a length of 9-10cm totaling 20 fish in 2 replications. Quantitative data analysis using the Survival Rate (SR) formula or survival. The results of the study found that higher levels of detergent could cause tilapia to be unable to survive more than four days because tilapia were only able to adapt to the lowest detergent concentration range. Tilapia will die if they are not able to adapt to the presence of detergent doses in water bodies and decreased dissolved oxygen.Keywords: Pollution Materials (Detergent), Tilapia (Oreochromis niloticus), Survival.